The true story of the 3 little pigs - Scieszka, Jon.; Smith, Lane (New York, N.Y., U.S.A. : Viking Kestrel, 1989)
The wolf gives his own outlandish version of what really happened when he tangled with the three little pigs.
Keywords: Wolves -- Fiction; Pigs -- Fiction